The Application of Problem-Based Learning in Soft Skills Courses: An Experiment in Classes with Multidisciplinary Students in Vietnam - Dang, Thi Van; Phung, Tran Gia Bao; Vu, Dinh Minh; Nguyen, Thi Thanh Tu (International Journal of Engineering Pedagogy (iJEP), 2025)
Soft skills are essential if graduates are to meet the demands of the 21st-century workforce. This represents a major challenge for higher education programs, which need to adopt teaching methods that effectively equip students with these essential skills. This study evaluates the impact of a problem-based learning approach to curriculum design on soft skills for multidisciplinary students. The elective course, which attracts a diverse cohort of students, is delivered in a blended learning format. Using a mixed-methods research approach, the study collected data via questionnaires from 140 multidisciplinary students split between experimental and control groups, supplemented by in-depth interviews conducted after the course. This paper describes a proposed teaching process based on problem-based learning and details the implementation of an experimental lesson on time management as part of the soft skills curriculum. The results indicate that problem-based learning not only enhances the development of soft skills but also encourages student initiative and creativity by improving individual and teamwork skills in both online and face-to-face learning environments. Based on these findings, the study recommends further research to broaden the application of problem-based learning in higher education contexts.